Pasien Kanker Payudara : Resiliensi dan Stress Menghadapi Kemotrapi - Merlitha, Nesi; Oktaviana, Rina (Jurnal Ilmiah Psyche, 2018)
This study aims to determine the relationship between the resilience with stress patients breast cancer undergoing chemotherapy hospitalized in the Hospital Dr. Mohammad Hoesin Palembang.“The population in this study were 100 patients with breast cancer and sampled as many as 78 people were obtained throughtechnique. proportionate stratified random sampling. Measuring instrument used in this study is a resilience scale and standard scale of perceived stress scale (PSS-10). Mechanical analysis using simple regression analysis techniques. The results of the analysis, showed a correlation coefficient (r) of 0.394 with a coefficient of determination (R square) of 0.155, and p = 0, 0000 p <0.01 on a two-lane Anova test. This suggests that the hypothesis is accepted. Results of the analysis showed that there was a significant relationship between the resilience with stress patients breast cancer undergoing chemotherapy hospitalized in the Hospital Dr. Mohammad Hoesin Palembang